ESCAPE BEHAVIOR OF THE LIZARD PHYLLOPEZUS POLLICARIS POLLICARIS (SPIX, 1825) IN REMNANTS OF THE CAATINGA BIOME - Silva, Adilson de Oliveira; França, Lucas de Melo; Conceição, Breno Moura da; Ferreira, Anthony Santana (Revista Nordestina de Zoologia, 2012)
We analyzed the escape behavior of the lizard Phyllopezus pollicaris pollicaris (Spix, 1825), by using field observations. This species has nocturnal habits and is generally found on rocky outcrops. We aimed to evaluate the escape behavior of the lizard P. pollicaris under a possible threat of predation, and check if it varies according to: (I) the kind of shelter, (II) the size of individuals (III) and the distance from the individual to the shelter. Regardless the size of the individual, the decision of when to flee was performed in the same way by the lizards, stating that the pattern is the same between juveniles and adults. Analyses showed that as closer to the shelter less is the distance between the observer and the lizard, and there is probably no preference between adults or juveniles regarding the shelter when they are escaping from predators.